La eutanasia es un hecho ilícito en el Derecho colombiano (2021)
Euthanasia in Colombia, unlike in the Netherlands, is not the result of a cultural consensus that arose from society itself, but rather an initiative of the Constitutional Court through its jurisprudence. Thus, the Constitutional Court, by issuing order through its jurisprudential rulings to the Ministry of Health and social protection, to regulate the organization and operation of an interdisciplinary committee in Hospitals, Clinics, IPS, EPS in relation to Euthanasia in Colombia, in addition to opposing to our religious culture; undoubtedly, it is incompatible with the constitutional principle of legality, enshrined in arts. 6, 90, 121, 122, 124, and 230 (C.N. of 1991), arts. 4°, 5° y 13, law 153/1887 and art. 32, law 57/1887.